2009
DOI: 10.1002/biot.200800130
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo expansion of adipose tissue‐derived stem cells in spinner flasks

Abstract: Recent reports indicate that adipose tissue is a novel source of multipotent stem cells that can be used in cell therapy and tissue engineering. However, using the traditional cultivation of adipose tissue-derived stem cells (ADSCs), it is hard to meet the needs of clinical applications. To obtain a large number of ADSCs while retaining their stemness, we seeded ADSCs in collagen/chitosan scaffolds and compared the proliferation of ADSCs in a 3-D static environment in dishes and a 3-D dynamic environment in sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 37 publications
0
16
0
1
Order By: Relevance
“…Our results are in agreement to the one of Siegel et al () who recently reported the expression of Oct‐4, Nanog mRNA in BM‐MSCs to be much lower compared to pluripotent stem cells and Sox2 mRNA to be minimally detected in a number of BM‐MSC preparations. Similarly, Vicente López et al () and Zhu et al (), both working with human adipose‐derived stem cells (ASCs) though‐found: the former have no change on the expression of Nanog and Oct‐4 with low doses of bone morphogenetic protein (BMP) in their ex vivo expansion study and the latter additionally examined Sox‐2 and Rex‐1, which remained unaltered in a spinner flask cultivation.…”
Section: Discussionmentioning
confidence: 98%
“…Our results are in agreement to the one of Siegel et al () who recently reported the expression of Oct‐4, Nanog mRNA in BM‐MSCs to be much lower compared to pluripotent stem cells and Sox2 mRNA to be minimally detected in a number of BM‐MSC preparations. Similarly, Vicente López et al () and Zhu et al (), both working with human adipose‐derived stem cells (ASCs) though‐found: the former have no change on the expression of Nanog and Oct‐4 with low doses of bone morphogenetic protein (BMP) in their ex vivo expansion study and the latter additionally examined Sox‐2 and Rex‐1, which remained unaltered in a spinner flask cultivation.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, due to the low number of cells and the invasive method required to isolate them, alternative sources of MSCs have been investigated. Cells with similar proprieties have been isolated from a broad range of tissues like skin [10, 11], peripheral blood [12], umbilical cord blood [13], muscle [14], adipose tissue [15], placenta [16, 17], dental pulp [18] or liver [19], and others. The differences in isolation protocols and tissues of origin lead to numerous definitions and use of various terms to refer to these cells such as mesenchymal stem cells, mesenchymal progenitor cells, or mesenchymal stromal cells.…”
Section: How Do We Define Mesenchymal Stem Cells?mentioning
confidence: 99%
“…Chondrogenic differentiation was induced by IMDM consisting of 0.1 μM dexamethasone, 50 μg/mL vitamin C, 100 μg/mL sodium pyruvate, 10 ng/mL transform growth factor (TFG-β3), 500 ng/mL bone morphogenetic protein (BMP-6), and 50 mg/mL ITS + , and detected by toluidine blue staining after 1, 2 and 3 weeks of induction, respectively. Adipogenic differentiation was induced by IMDM including 10% FBS, 0.1 mM 3-isobutyl-1-methyl xanthine, 1 μM dexamethasone, 0.2 μM indomethacin, and 10 μM insulin, and assayed with oil red staining after 1, 2 and 3 weeks of induction, respectively [15,16].…”
Section: Multilineage Differentiation Potential Of Expanded Adscsmentioning
confidence: 99%